The Impact of Water Quality Detorioration in Mangrove Forest in Semarang Coastal Area - Kenanga Sari; Tri Retnaningsih Soeprobowati (Indonesian Society of Limnology, 2021)
The fast-growing development and industrialization have caused various impacts on nature including heavy metal pollution, especially in the coastal area. Tambakredjo, located in the North Semarang city, is home to a large number of mangrove and animal species. Therefore, water quality is important. This study was conducted to analyze water quality in the coastal area of Tambakredjo based on physical and chemical measurements. Water quality data were collected from different sites. Physical parameters (temperature, pH, DO, EC, TDS, ORP and salinity) and chemical parameters (Total N, Total P, Pb, Cr, Cd) were observed. Multivariate statistical techniques, including Principal Component Analysis (PCA), was applied to evaluate water quality. The results showed first principal component is 76.27%, where the highest conductivity, total dissolved solids and salinity are associated with site 1. Content of Lead 1.289 ppm, Cadmium 0.021 ppm, and Chromium 0.352 ppm exceeds the water quality standard PP. No. 82/2001. It indicated that Site 1 was characterized as the most heavily polluted site because the location received pollutants from rivers and oceans. This study also examined the short-term changes of the mangrove-covered area at the side of Banjir Kanal Timur using historical map satellite images. The results show that mangrove coverage in Tambakredjo near the aquaculture area had decreased from 1,875m2 to 1,401m2. Meanwhile, on the other site, the mangrove planting effort as a restoration program is carried out, especially in the estuary of Banjir Kanal Timur to anticipate more environmental changes.